Statistical review of radiology registrars after hours computed tomography reporting accuracy - Terreblanche, Owen Dale (My University, 2012)
Background: There is a heavy reliance on registrars for afterhours CT reporting with a resultant unavoidable error rate. This study was done to determine this error rate. Material and Methods: A 2 month prospective study was undertaken. Provisional CT reports issued by the registrar on call were reviewed information relating to the errors made during the call were recorded and analyzed. Results: 1477 CT scans were performed with an overall error rate of 17.1%. A significant difference was found between trauma (15.8%) compared to non-trauma scans (19.2%). The difference between emergency scans (16.9%) and elective scans (22.6%) was not significant. Abdominopelvic scans elicited the highest error rate (33.9%). Increasing workload resulted in a significant increase in error rate. Missed findings were the most frequent errors (57.3%). Error rate decreased with increasing year of training.
A Research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in Diagnostic Radiology. Johannesburg, 2012
Keywords: Radiology--case reports; Medical Staff, Hospital